ANALISIS BAURAN PEMASARAN DALAM MENINGKATKAN JUMLAH PENJUALAN PADA PT. GANDUM JAYA MAKASSAR - Sudirman Sudirman (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2014)
The purpose of this study was conducted to determine the marketing mix consists of product, price, promotion and distribution of the PT. Wheat Jaya Makassar in increasing the number of cigarette sales. Based on existing sales forecasts in Table 4, it appears that the years 2013 to 2017 sales continue to rise. In 2013 sales reached 221 132 ball, ball in 2014 rose to 224 399, rising to 227 666 2015 ball, 2016 rose to 230 933 ball and in 2017, rising to 234 200 ball. Analysis of the marketing mix PT. Wheat Jaya Makassar consisting of product, price, promotion and distribution quite well, while product sales forecast for the wheat brand cigarettes next five years ie in 2013 and 2017 is promising or has a promising future